2016
DOI: 10.1007/s11664-016-4924-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Al2O3 and Li3BO3 Content as Sintering Additives of Li7−x La2.95Ca0.05ZrTaO12 at Low Temperature

Abstract: Simultaneous effect of Al2O3 and Li3BO3 addition on sintering behavior and Li-ion conductivity of Li7-xLa2.95Ca0.05ZrTaO12 (LLCZT) garnet electrolyte sintered at 900 °C (10 h) is evaluated. Crystal phase and microstructure of the different composites were evaluated by X-ray diffraction (XRD) and scanning electron microscopy (SEM), respectively. Electrical properties of the composites with high relative densities (95 %) were examined by impedance spectroscopy (EIS). Cubic phase was formed for LLCZT 1 2 3 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 21 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…One of the most popular glass used as an additive material seems to be Li3BO3, denoted later as LBO, due to its low glass transition and melting temperatures. N. C. Rosero-Navarro et al [31,32] studied the composites based on garnet-type material and formed in the system Li7La3ZrxM1-xO12 -Li3BO3 (M = Nb, Ta). They reported that the value of ionic conductivity of ceramic Li7La3Zr2O12 (LLZO) sintered at 900°C is relatively low, ca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most popular glass used as an additive material seems to be Li3BO3, denoted later as LBO, due to its low glass transition and melting temperatures. N. C. Rosero-Navarro et al [31,32] studied the composites based on garnet-type material and formed in the system Li7La3ZrxM1-xO12 -Li3BO3 (M = Nb, Ta). They reported that the value of ionic conductivity of ceramic Li7La3Zr2O12 (LLZO) sintered at 900°C is relatively low, ca.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to obtain highly conductive material, another approach has been proposed. It is based on the addition of some foreign phase into the base matrix in order to lower the grain boundary resistance [24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Garnet-type Li +ion-conducting Li 7 La 3 Zr 2 O 12 -based ceramics have been prepared by sintering at about 700-900°C with several additives such as Li 3 BO 3 23-25 and lithium borosilicate based glasses. 26,27 These liquid-phase sintered ceramics show high conductivities approaching those of high-temperature-sintered ceramics (generally 1100-1200°C). Moreover, these sintering techniques do not require expensive apparatus like hot-pressing or spark plasma sintering.…”
Section: Introductionmentioning
confidence: 99%
“…The activation energy is 0.31 eV (estimated from log(σT) vs 1/T), which is a typical value for the cubic garnet LLZ solid electrolyte doped with calcium and tantalum. 23,36 The ionic conductivity and activation energy of the LS/LLCZT/LS pellet suggest that lithium silicate does not significantly affect the electrical properties of the LLCZT pellet.…”
Section: Resultsmentioning
confidence: 97%
“…The LLCZT solid electrolyte was synthesized by the liquid-phase process, following a similar protocol described in a previous report. 23 LiNO 3 (99%, Kanto Chemical Co.), La(NO 3 ) 3 •6H 2 O (99.9%, Kanto Chemical Co.), Ca(NO 3 ) 2 (99%, Wako), Zr(OC 4 H 9 ) 4 (85% in butanol, Wako), Ta(OC 2 H 5 ) 5 (99.9%, High Purity Chemicals), and Al(OCHCH 3 C 2 H 5 ) 3 (95.0%, Kanto Chemical Co.) were used as precursors. The ethyl acetoacetate (EAC, 99.0%, Kanto Chemical Co.) was used as a stabilizing agent for the alkoxides.…”
Section: Methodsmentioning
confidence: 99%